BATIK MOTIF DESIGN WITH CHARACTERISTICS TIONGHOA CULTURE USING VECTOR ART TECNIQUE - Deli Deli; Christine Christine (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
Batik motif is a work of art from traditional time till now, one example of tradition batik motif which is the Tionghoa cultural. See from our techonology now, can design by using one of the technology drawings aplication system. In this case study, the purpose was to design batik motifs in Tionghoa cultural by using a drawing application system, which is Adobe Illustrator CS6 and use vector art techniques. This research uses the R&D method where at this stage the design will be designed, validated, revised, and product tested. The final result will be a photo in the form of a JPEG or PNG that has been designed in the application.